Pamięć u źródła mitu. Świadomość historyczna Izraelitów w Thomasa Manna Józefie i jego braciach - Makowski, Tomasz (Humaniora. Czasopismo Internetowe, 2025)
Memory plays a significant role in Thomas Mann’s biblical tetralogy Joseph and his Brothers (1933–1944) due to its direct relationship with the line of tension between the mythical plot material and the convention of a realistic historical novel, which is fundamental to the work. For the purpose of analysis the author used the tools of anthropological reflection on memory, developed by the Egyptologist Jan Assmann and presented in his book Cultural Memory and Early Civilization. Writing, Remembrance, and Political Imagination (2008). The aim of the article is to show that the image of memory included in the novel is not only an element of the cultural staffage, but has also been used to a great extent to overcome the aforementioned conflict of myth and historical realism.